2005
DOI: 10.1002/mrc.1661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative EPR study of Cu@C60 and N@C60 endofullerenes

Abstract: A comparative study of C60-based endohedral fullerenes was performed. From an analysis of spin relaxation times of the recently characterized Cu@C60 metallo-endofullerene, it could be shown that the encased ion occupies a well-defined off-centre position even at room temperature. Localization on the timescale of an EPR experiment is combined with charge transfer of approximately two electrons, resulting in the EPR signature of a 3d9 copper ion. This is in contrast to N@C60, for which a nearly complete decoupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…So the most stable Cu@C 24 is the 1b isomer in C s symmetry with 2 AЈ state. In the most stable Cu@C 24 , the distance between Cu atom and center is about 0.28 Å, which is agreement with the ESR measurements obtained by Knapp et al, [52] who shown that the encased copper atom occupies a well-defined off-center position even at room temperature.…”
Section: Table I ____________________________________________________supporting
confidence: 89%
“…So the most stable Cu@C 24 is the 1b isomer in C s symmetry with 2 AЈ state. In the most stable Cu@C 24 , the distance between Cu atom and center is about 0.28 Å, which is agreement with the ESR measurements obtained by Knapp et al, [52] who shown that the encased copper atom occupies a well-defined off-center position even at room temperature.…”
Section: Table I ____________________________________________________supporting
confidence: 89%
“…The Cr atom is deviated from the center of C 24 cage by about 0.311 Å , which is similar to those of TM@C 24 (TM = Mn, Fe, Co, Ni, and Cu) [11] and Ti@C 24 [13]. Further, it is also agreement with the ESR experiments prepared by Knapp et al [61], who reported that the encased copper ion occupies a well-defined offcenter position even at room temperature.…”
Section: Optimized Equilibrium Geometriessupporting
confidence: 86%
“…Thus, the first reaction step (step 1 in Scheme 1) begins from N@C 60 1, which can exist in high-(spin 3/2) and low-spin (spin 1/2) states. It has been shown in previous experimental 2, [70][71][72] and theoretical 4,73,74 studies that the ground state of 1 is high spin. Our current study supports this conclusion, since 4 1 is more stable than 2 1 (see Scheme 2) by 26.0 kcal mol À1 Scheme 1 Proposed approach for step-by-step synthesis of NH 4 + @C 60 À (13).…”
Section: Mechanism Of Proton Penetration and Nitrogen Escapementioning
confidence: 87%